Heat Transfer Experiments on Electric Aircraft Battery Minichannels with Ethylene Glycol-Air Fluid - A , Dhawysulthan M; Marausna, Gaguk; Jayadi, Farid; Sitepu , Eric Leonardo; Adi Kusuma, Muhamad Bayu (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2022)
The aviation industryhas changed the mass and private transportation industry, thus making aircraft more and more varied, this type of air transportation has a very high adverse effect on the atmosphere because of its very high fuel consumption and emitting so many pollutantsthat aircraft for the future will lead to There are 2 types of aircraft, namely  Hybrid-Electric  Aircraft  and All-Electric  Aircraft. Both  have the  same electric power  drive, but  there  are  weaknesses  in  this  transportation.  Namely  on  the  battery  used.  The  method  used  is  the experimental  method.  While  this  type  of  research  uses  an  electric  aircraft  battery  prototype  where  the temperature of the working fluid will be measured with a thermocouple 1 (T1) and flowed by a pump from tank 1 to  the  minichannel  in  thebattery  pack.  For  the  battery,  the  temperature  will  be  measured  by  thermocouple  2 (T2), thermocouple 3 (T3), and thermocouple 4 (T4) then the working fluid from the minichannel will be flowed into tank 2 where the temperature will be measured using thermocouple 5 (T5). The results obtained in this study are the use of working fluid 75% Ethylene Glycol –25% Water is better than 75% Water –25% Ethylene Glycol in  terms  of  pressure  drop,  temperature  value,  and  heat  transfer  convection  itself.  Meanwhile,  for the  working fluid  flow  velocity  and  Reynolds  Number,  the  working  fluid  is  75%  Ethylene  Glycol –25%  Water  better  than 75% Water –25% Ethylene Glycol